Contextual factors of analytical and entrepreneurial thinking in science learning - M. Noris; Asnafiyah Asnafiyah; Dwi Setyo Astuti; Gufran Gufran; Syarifuddin Syarifuddin (Journal of Educational Management and Instruction (JEMIN), 2026)
The development of analytical and entrepreneurial thinking is increasingly important in science education because students are expected to analyze complex problems, generate innovative solutions, and translate ideas into practical actions. However, these cognitive competencies may be shaped by diverse social, environmental, behavioral, and educational conditions, which can differ across school contexts. This study examines the factors associated with students’ analytical-thinking and entrepreneurial-thinking skills in boarding and non-boarding schools. A quantitative approach was employed using an 89-item questionnaire administered to 208 senior high school students selected through random sampling from boarding and non-boarding schools in Indonesia. The data were analyzed using structural equation modeling with partial least squares (PLS-SEM) through SmartPLS. The findings indicate that the patterns of influence differed substantially between the two school contexts. In boarding schools, environmental, social, parenting, health, lifestyle, and other contextual factors collectively explained 25.5% of the variance in analytical thinking and 86.4% in entrepreneurial thinking. In non-boarding schools, the corresponding explanatory power was 86.5% for analytical thinking and 23.1% for entrepreneurial thinking, with parenting showing a particularly strong association with analytical thinking. These findings suggest that students’ cognitive and entrepreneurial development is closely connected to their learning and social environments. Schools should therefore strengthen supportive learning environments, family engagement, healthy habits, and student-centered instructional practices to foster higher-order thinking competencies.